(NwOLNY \LEKTRI^ESKOGO PROBOQ W OGRANI^ENNOJ PLAZME (B/s - (NlAGARXKOW(B, (NaNDREJ nIKOLAEWI^s; (NsTAROSTIN(B, (Na(B. (Nn(B.s ((NmOSKWA (B:s (NnAUKA (B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 197-203 (144 (NNAZW(B.)s
Keywords: (NwOLNOWYE PROCESSYs; (NgAZY (B- (NpROBOJ \LEKTRI^ESKIJs; (NpLAZMA (B((NFIZ(B.) (NGAZORAZRQDNAQs